Analisis Aksiologi dalam Filsafat Ekonomi Islam: Integrasi Nilai Keadilan, Etika, dan Kesejahteraan dalam Pembangunan Ekonomi Berkelanjutan - Putri Azkia Risyda; Raihana Azzahra; T. Razita Syahinda (Journal of Islamic Economics and Finance, 2025)
This writing aims to describe how the importance of the role of Axiology in planning sustainable economic growth, especially in preventing adverse impacts that can occur in the future. This study is a literature review using a qualitative approach with a descriptive type. conducting document study data collection techniques where the process of searching for data through internet media to obtain information based on references, journals, articles or books online related to the object of analysis. The results of this study show that the concept of axiology in Islamic economic philosophy not only has a role in directing individual behavior in economic activities, but also seeks to build a more just and sustainable economic system. The current economic development is not enough to be fully felt by the community. So that the integration of the values of Justice, Ethics and Welfare has not been fully realized. Therefore, the existence of SDG is a planned agenda that aims to prosper the community through the development of the Social, Economic, Environmental and governance sectors carried out by the government.